PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS III SEKOLAH DASAR MELALUI MEDIA JEMURAN HITUNG PADA MATERI PERKALIAN - Nabila Nurul Aida; Ahmad Hariandi; Akhmad Faisal Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the mathematical concept understanding of third-grade elementary school students through the use of the "Counting clothesline" media on multiplication material. The main problem in this research is the low understanding of students towards basic multiplication concepts, which tend to be rote memorization. The methodology used is a quasi-experimental design with a Nonequivalent Control Group Design. The research sample consisted of class III A as the experimental class and III B as the control class. The results showed a significant increase in concept understanding in the experimental class compared to the control class. This is evidenced by the t-test results on the N-Gain Score which showed a Sig. (2-tailed) value < 0.001. In addition, the Effect Size test showed a value of 1.379, which is in the very large effect category. Thus, the " Counting clothesline " media is effective in improving students' mathematical concept understanding.